Prognostic Value of High-sensitivity C - reactive protein in Acute ST-segment Elevation Myocardial Infarction in Hospitalized Patients - Basak, Shishir Kumar; Akhtaruzzaman, KM; Kundu, Ashok Kumar; Dey, Sudhangshu Ranjan; Uddin, Md Faruque (Medicine Today, 2013)
Acute Myocardial Infarction (AMI) is an inflammatory condition. C-reactive protein (CRP) is a sensitive inflammatory marker. Elevated plasma CRP levels detected in the first few days of AMI is a predictor of unfavourable short and long term outcome. This cross sectional comparative study included 60 patients of 28-85 years with acute ST segment elevation myocardial infarction (STEMI) admitted within 24 hours of onset of chest pain in coronary care unit (CCU) of Sylhet MAG Osmani Medical College Hospital. Based on high-sensitivity C-reactive protein (hS-CRP) levels on the first day, the patients were divided into two groups: Group-I Low hs-CRP group (?10 mg/L, n=22); Group-II High hs-CRP group (?10 mg/L, n=38). Clinical and echocardiographic prognostic variables were compared between two groups. The mean values of 1st and 3rd day hs-CRP levels of acute STEMI patients who developed the worse outcomes and who did not develop the outcomes are also compared. Among the in-hospital outcomes in group-I and group-II, (recurrent angina, cardiogenic shock, heart failure (HF), arrythmias, left ventricular ejection fraction (LVEF), wall motion abnormality (WMA), hospital stay and mortality) only arrhythmia was found significantly higher in high hs-CRP group (36.4% vs 76.3%, P<0.01). On the other hand, the patients who developed these worse outcomes had significantly higher mean values of both 1st day and 3rd day hs-CRP compared to those who did not develop these outcomes. Mean values of 1st and 3rd day hs-CRP (mg/L) of patients who develops recurrent angina or not was 68.42 (SD 12.56) and 110.14 (SD 10.66) vs 29.08 (SD 5.83) and 36.74 (SD 6.64) p<0.01. Among patients with arrhythmias, the values were 62.77 (SD 9.06) and 83.94 (SD 10.0) vs 14.23 (SD 2.92) and 35.20 (SD 7.65) p<0.001. Hs-CRP can be used as a simple and cost effective tool for prediction of in-hospital prognosis in patients with acute STEMI. DOI: http://dx.doi.org/10.3329/medtoday.v24i1.14113 Medicine TODAY Vol.24(1) 2012 pp.36-39